Variation in pre-extraction processes influences the differences in chemical constituent, quantity and biochemical activities of volatile oils from Crinum jagus (Th.) D.: Gas Chromatography-Mass Spectrometry analysis. Issue 6 (2nd November 2018) - Oladimeji, Abdulkabir Oladele
ABSTRACT: A comparative study performed on essential oil composition, cytotoxic and antioxidant activities of fresh and dried samples involving leaf and bulb of Crinum jagus (Th.) D. were reported. Qualitative and quantitative variations in the composition of oils were investigated using GC and GC-MS. The oil extracted from the leaf of C. jagus's was characterized by high proportions of beta-ocimene (10.0–13.8%), followed by hexadecane (2.6–11.1%), tetramethylpentadecane (9.3–10.4%) and phytol (7.0–9.0%). Bulb oil is rich in 14-methylpentanedecanoic acid methyl ester (20.6–22.5%), tetratetracontane (7.9–10.0%) and 9, 12-octadecadinenoic acid (14.0–14.2%). Dried leaves and dried bulbs exhibited the highest cytotoxic activity (IC50 of 0.002 and 0.003 µg/mL, respectively) followed by fresh leaves 0.033 µg/mL and fresh bulb 0.55 µg/mL. The essential oils at 1.0 mg/mL displayed significant antioxidant activities. The level of antioxidant capacity varied according to samples. The chemical constituents and quantities significantly varied based on sample pre-extraction processing, thus affecting the biochemical activities.